Serum high-sensitivity C-reactive protein as a biomarker in patients with metabolic syndrome: evidence-based study with 7284 subjects - Mirhafez, S R; Ebrahimi, M; Saberi Karimian, M; Avan, A; Tayefi, M; Heidari-Bakavoli, A; Parizadeh, M R; Moohebati, M; Azarpazhooh, M R; Esmaily, H; Nematy, M; Safarian, M; et al. (European journal of clinical nutrition, 2016)
Background/Objectives: Metabolic syndrome (MetS) is characterized by abdominal obesity, dyslipidemia, hypertension and glucose intolerance, and is associated with an increased risk of developing cardiovascular disease (CVD), diabetes mellitus and related diseases. Circulating levels of inflammatory markers such as C-reactive-protein (CRP) have reported to be associated with CVD. Against this background, the prevalence of MetS is increasing globally, and thus predictive biomarkers are required for identification of MetS patients at an increased risk. Here we explored the value of CRP as a biomarker in 7284 subjects and also investigated which features of MetS have the greatest association with the hs-CRP level. Subjects/Methods: The subjects were recruited from the Mashhad stroke and heart atherosclerotic disorder study. Anthropometric factors and biochemical parameters (for example, high-sensitivity CRP (hs-CRP), high-density lipoprotein/low-density lipoprotein, triglycerides (TGs) and fasting blood glucose (FBG)) were determined. Univariate and multivariate analyses were conducted to evaluate the association of hs-CRP and MetS. Results: Our results illustrated that the concentration of serum hs-CRP increased progressively with the number of MetS components, and subjects who fulfilled the criteria of MetS for waist circumference, TGs, blood pressure and FBG were found to have hs-CRP of 0.53, 0.38, 0.34 and 0.71 mg/l, respectively, higher than matched-subjects. Importantly, FBG had the greatest association with hs-CRP concentration. Conclusions: Our data demonstrate the significant association between MetS components with hs-CRP, indicating that this association was cumulative by increasing the number of the defining features of MetS, supporting further studies to explore the value of emerging marker as a novel method for detecting individuals at high risk of developing MetS.